FACEBOOK MARKETPLACE AS AN ALTERNATIVE TO ADVANCE THE ECONOMY OF THE UMAM: PERSPECTIVE OF ISLAMIC ECONOMIC LAW - Indra, Indra; Iska, Syukri; Dayat, Dayat; Arianti, Farida (Universitas Muhammadiyah Prof DR HAMKA, 2024)
Transaction sell purchase is done using the Facebook marketplace platform is very structured big in use technology information as well as the internet at the moment this. Development method marketing product mature this is not it regardless from pattern sell buy and transaction online make law Islam take very important role in respond in perspective law economy Islam. On the basis Islam allow all form transaction muamalah is what is done, as long as Not yet There is the text forbids it transaction that. Facebook Marketplace give solution in promote product seller to get it reachable by buyers with fast and flexible and legal Islam give limitations to transaction the with exists terms and conditions sell buy in Islam, as long as transaction That fulfil provision terms and conditions so transaction the allowed in Islamic and also legal